Apomictic species of Alchemilla from the High Atlas Mountains: revision of the genus Alchemilla ( Rosaceae ) in Morocco - Angel Romo (Plant and Fungal Systematics, 2021)
A taxonomic revision of the Alchemilla in the High Atlas Mountains has been carried out. This genus is represented in Morocco by Alchemilla atlantica , A. gourzai , A. litardieri , A. mairei and by a new taxon A. boratynskii , sp. nov., described here from the High Atlas Mountains range. Data on their chorology, ecology and phenology, as well as an identification key, are provided. The conservation status of this newly described narrow endemic and the other four taxa, also endemics previously known from the Moroccan Atlas Mountains, is provided. Alchemilla hirtipes should be excluded from the flora of Morocco.